Carotid intima-media thickness in young patients with familial hypercholesterolaemia. - Lavrencic, A. (1996)
OBJECTIVE: To assess the extent of early atherosclerotic changes of the carotid arteries in young patients with familial hypercholesterolaemia (FH) detected as increased intima-media thickness (IMT), and to determine the relations between IMT and some clinical and blood variables such as lipid and lipoprotein(a) (Lp(a)) concentration and haemostatic factors. DESIGN: The IMT of the carotid bifurcation, the proximal 1 cm of the internal carotid artery, and the distal 1 cm of the common carotid artery was determined in all subjects using B mode ultrasonography. Blood lipids, fasting glucose, and several haemostatic variables were also analysed. SUBJECTS: 28 patients with FH (12 males and 16 females aged 11 to 27 years, one homozygote, 27 heterozygotes) and 28 sex and age matched normolipidaemic healthy subjects. RESULTS: The mean carotid IMT (the average of six measurements of the maximum far wall IMT in the three carotid segments on each side) was significantly greater in patients with FH than in controls (mean (SD) 0.71 (0.15) v 0.49 (0.08) mm, P < 0.001). In all subjects, the mean IMT was significantly correlated with total cholesterol (r = 0.59), low density lipoprotein (LDL) cholesterol (r = 0.60), triglycerides (r = 0.27), and systolic blood pressure (r = 0.47). No correlation was found between the mean IMT and Lp(a), fibrinogen, tissue plasminogen activator, and plasminogen activator inhibitor 1. CONCLUSIONS: The majority of young patients with FH have a greater intima-media thickness of the carotid arteries than healthy subjects. Since the individual susceptibility of patients with FH to increased LDL cholesterol is different, B mode ultrasonography could provide a useful tool to identify those who are more likely to develop premature atherosclerotic disease.